2023
DOI: 10.1039/d2gc03694k
|View full text |Cite
|
Sign up to set email alerts
|

Micelle-mediated multicomponent cross-coupling in water: general construction of 3-chalcogenylindoles

Abstract: A general and sustainable multicomponent cross-coupling for the construction of 3-chalcogenylindoles from indoles with aryl iodides and elemental sulfur under the aqueous micellar condition was developed. The elemental sulfur is...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 73 publications
0
3
0
Order By: Relevance
“…70,71 Although enhanced reaction activity is achieved, the catalytic selectivity is not well-controlled. Bimetallic NPs stabilized in aqueous micellar medium were further designed, [72][73][74][75] and their activity and selectivity can be affected by modulating the NP surface free energy, regulating the metal-organic interaction arising from surfactant modifiers and increasing the solubility of hydrogenation gas in water. Recently, Handa et al 76 reported that bimetallic Ni(0)Pd (0) NP catalyzed highly selective 1,4-reductions of a variety of Michael acceptors can be processed successfully under aqueous micellar conditions.…”
Section: Introductionmentioning
confidence: 99%
“…70,71 Although enhanced reaction activity is achieved, the catalytic selectivity is not well-controlled. Bimetallic NPs stabilized in aqueous micellar medium were further designed, [72][73][74][75] and their activity and selectivity can be affected by modulating the NP surface free energy, regulating the metal-organic interaction arising from surfactant modifiers and increasing the solubility of hydrogenation gas in water. Recently, Handa et al 76 reported that bimetallic Ni(0)Pd (0) NP catalyzed highly selective 1,4-reductions of a variety of Michael acceptors can be processed successfully under aqueous micellar conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Designing ligand-free micellar Pd NPs involves the synergistic effect of metal NPs and aqueous micellar media to improve the activity in the reaction. 40,41 The main factors include (i) the chelation effect between NPs and micelles, (ii) the size effect of NPs, and (iii) the isolation effect of micelles on substrates. [42][43][44][45][46][47] Due to their high surface-to-volume ratio, the reactivity of NPs increases, while it would affect the stability of NPs.…”
Section: Introductionmentioning
confidence: 99%
“…48,49 The chelation of ultrasmall metal NPs with micelles can prevent the agglomeration of NPs to enhance their stability and ensure more active centers. 13,41 Besides, the isolation effect of micelles protects the organic substrates and intermediates in the hydrophobic core, so that the local high concentration is stably dispersed in the aqueous phase, providing a self-assembled nanoreactor to facilitate substrate-catalyst interaction. 11,[50][51][52][53][54] From the perspective of scalability, in situ preparation of ultrasmall NPs chelated with micelles has more application prospects than the current expensive and inconvenient procedures.…”
Section: Introductionmentioning
confidence: 99%